Expression of Zahiriddin Babur’s Spirit in The Literary Work by Alex Rutherford - Khayrullayeva Kamola Ravshanovna (International Journal Of Literature And Languages, 2025)
This article examines the first book of the epic novel "Empire of the Moghul" by English writer Alex Rutherford, "Raiders from the North," dedicated to the life of our great ancestor, Zahiriddin Babur. At the same time, the depiction of Babur's mental state during his childhood, adolescence, reign, and military rule is analyzed.